The Impact of Corporate Governance on Financial Performance of Financial Institutions in the EU - Musayev, Polad; Masimov, Vugar; Alisoy, Nargiz; Hasanli, Aysel (ADA University, 2022)
Corporations have been under a higher level of scrutiny since the financial crisis of 2008-2009. Despite the fact that wrongdoings and unethical behavior of various corporations have been under the limelight prior to the crisis as well, the most recent financial crisis shed light on the drawbacks of the current systems of corporate governance and revealed a need for the introduction of different mechanisms for the purpose of evaluating and overseeing the activities of firms. Financial institutions, in particular, have been under focus as these organizations were the main culprit of the occurrence of the financial crisis with their excessive risk-taking and poor corporate governance mechanisms. Having this mind, institutions both in the US and the EU have introduced a new set of regulations in the post-crisis period with a purpose of reducing a conflict of interest in the management of financial institutions and improving the efficiency and effectiveness of corporate governance mechanisms of these organizations. This research has investigated how various corporate governance mechanisms impact financial performance of financial institutions in the EU. To conduct the research, 50 largest financial institutions in terms of market value have been selected for the study and a model from the empirical studies to date has been constructed which included such independent variables as duality of CEO and Director of the Board, the existence of the performance-based compensation, internal ownership, independent members of the Board, External Ownership, Board Size, Liquidity, Bank Size, Credit Risk and Ownership Concentration. Regarding dependent variables, ROA, ROE and net interest margin have been selected for the study framework. The latest data for the financial institutions has been taken for 2020 and correlation and regression analysis has been conducted in order to understand the relationship between variables. To summarize the findings of the research, a regression analysis that comprised of corporate governance variables (CEO duality, performance-based compensation, internal ownership, external ownership, independent board members, ownership concentration and size of the board) and control variables (such as bank size, credit risk, and liquidity) as independent variables have been constructed. ROA, ROE and net interest margin have been the determinants of profitability in this research. The analysis of data for 50 financial institutions, therefore, found that performance-based compensation, independent board members, ownership concentration and size of boards are corporate governance variables that improved profitability of banks in the EU and the impact was unanimous for all three profitability indicators. Liquidity and credit risk had a negative and significant effect on all three profitability measures. Finally, ownership types and CEO duality had no significant relationship with financial performance. The EU banks, therefore, have been advised to apply a greater level of performance based compensation, have more independent members on the board, increase and diversify board size, enlarge bank activities to achieve economies of scale, keep liquidity at least at an adequate level, and improve credit policy to reduce non-performing loans in the future. Overall, findings showed that several aspects of corporate governance significantly affect profitability of banks.
Keywords: Corporate governance.; Financial institutions.; Financial institutions -- European union.; Business